Isolation of Antithrombin III from Normal and α1-Antitrypsin-Deficient Human Plasma - Borsodi, Anna D.; Bradshaw, Ralph A. (Thrombosis and Haemostasis, 1977)
The plasma of individuals, hetero- or homozygous for α1-antitrypsin deficiency, contains greatly decreased amounts of antithrombin activity as assayed against factor Xa. However, heparin stimulation of the residual antithrombin activity is observed, which is comparable to that of normal plasma. Antithrombins isolated from both normal and α1-antitrypsin deficient plasma by a simplified procedure are indistinguishable in both properties and yields. The microheterogeneity observed on isoelectric focusing of both preparations can be eliminated by treatment with neuraminidase. Neither purified human antithrombin nor α1-antitrypsin, when assayed against bovine trypsin, is stimulated by heparin. These results clearly establish the unique natures of antithrombin and α1-antitrypsin and show that about 75% of the antithrombin activity measured in normal plasma is due to α1-antitrypsin. Estimates of anti thrombin III activity in normal plasma by assays dependent on enzymatic activity can probably be obtained only in the presence of heparin.